The Implementation of Natural Approach in Teaching Speaking - Zulkifli, Dadan; Triana, Lusi; Nurjanah (Arden Jaya Publisher, 2024)
The current research aims to find out the implementation of the Natural Approach in teaching speaking English and the problems that the teacher faced and how to solve the problems. This study uses qualitative data and uses narrative inquiry. This study uses observation and interviews as data collection methods. This study uses semi-structured interviews (open-ended questions) to collect more complete data. The research was held in the odd semester of 2023-2024 at SMK PGRI 1 Depok. The findings show that the participant implements the Natural Approach fitted to the six stages based on Richards and Rodgers. This current research found the four problems that the participant faced when teaching and some ways to overcome these problems. Key Words: learning outcomes, scramble-type cooperative, CTL